A meta-analysis of the effect of metacognitive instruction on mathematics achievement - Hidayat, Riyan; Mohd Saad, Mohd Rashid; Wewe, Melkior (Taylor and Francis, 2025)
Integrating metacognition into mathematics education is crucial for improving students’ mathematical performance, problem-solving abilities, and attitudes toward mathematics. The objective of this meta-analysis is to examine the overall impact of metacognitive instruction on mathematics performance. We conducted a systematic review using the PRISMA guidelines, searching through databases such as Web of Science, Scopus, ProQuest and Google Scholar. This yielded 43 studies involving 13,924 (experimental group, N = 7061; control group, N = 6863). We utilized R software packages to compute the effect size, employing standardized mean differences (SMD) and establishing 95% confidence intervals. Our findings demonstrate large and statistically significant effects of metacognitive instruction on mathematics achievement [ES = 1.11], metacognitive skills [ES = 1.18], and various other learning outcomes [ES = 1.27]. The results indicate that exploring this phenomenon could lead to notable enhancements in mathematics performance. These findings provide valuable insights for educators, informing them on how to optimize teaching methods and curriculum design to seamlessly integrate metacognitive instruction into mathematics education.